A wavelet‐based expert system for digital subscriber line topology identification. (28th April 2014) - Lima, V.D.; Klautau, A.; Costa, J.; Ericson, K.; Fertner, A.; Sales, C.
Summary: This work proposes a new method for automatically identifying topologies of lines with one or more sections in a telephone network. The method is based on the examination of both impulse response and time‐domain reflectometry trace of a line under test. They are analyzed using a method based on the wavelet transform that identifies and extracts features that contain information about the line topology. Those features are interpreted by an expert system composed of three sequential modules that estimate, respectively, the type of line makeup (serial or bridge tap), the lengths of the line sections, and the corresponding cable type, which are the parameters that completely identify the topology according to the assumed model. A thorough comparison with two state‐of‐the‐art methods is also presented using several twisted‐pair copper cables. The results show that the proposed method provides good accuracy with respect to topology identification at low computational cost. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : This work proposes a method for line topology identification in telephone networks. Basically, an expert system based on wavelet analysis (WES) interprets features resulting from different 'paths' taken by the input signal into the line, present both on impulse response and time‐domain reflectometry trace. In this way, the method estimates three parameters that completely identify the topology according to the assumed model. We also present a thorough comparison with two state‐of‐the‐art methods using several twisted‐pair copper cables.